Management accounting - Stice, James D.; Skousen, K. Fred.; Albrecht, W. Steve; Swain, Monte R. (Cincinnati, OH : South-Western College, 1999)
This book is about: Foundations of management accounting; Planning, Control, and Performance evaluation; and Other dimension of decision making.
Keywords: Accounting; Managerial accounting